Security and trust management : 13th International Workshop, STM 2017, Oslo, Norway, September 14-15, 2017, Proceedings /: 13th International Workshop, STM 2017, Oslo, Norway, September 14-15, 2017, Proceedings. (2017) - Unknown
No abstract available